2020
DOI: 10.26650/sj.2020.40.2.0101
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Skills Mismatch in Vocational Education in Turkey: The Reasons for Out-of-Field Employment

Abstract: As a type of skills mismatch, horizontal skills mismatch (HM) is a particularly important problem for vocational education and training (VET) in Turkey because the majority of VET graduates work in a different field than the one in which they were educated. This study aims to determine the reasons why some VET graduates in Turkey work in fields other than their original field of study. For this purpose, we have employed a sequential mixed-model research design, first conducting face-to-face interviews with 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…For example, since the problems in the transitions from school to work are considered to be predominantly associated with the quality of VET in Turkey, solutions are also expected from the VET since many years (Özer, 2018, 2019a, 2019bÖzer & Suna, 2019. However, the problems seem to be more related to the dynamics of the labor market rather than the VET itself (Özer, 2020a, 2020b, 2020c, 2020dSuna, Tanberkan, Ero¤lu, Özer, & Gür, 2020b). Worse still, as the education is held macroscopically responsible for the difficulties in school-to work transitions, the individuals are held microscopically responsible for their unemployment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, since the problems in the transitions from school to work are considered to be predominantly associated with the quality of VET in Turkey, solutions are also expected from the VET since many years (Özer, 2018, 2019a, 2019bÖzer & Suna, 2019. However, the problems seem to be more related to the dynamics of the labor market rather than the VET itself (Özer, 2020a, 2020b, 2020c, 2020dSuna, Tanberkan, Ero¤lu, Özer, & Gür, 2020b). Worse still, as the education is held macroscopically responsible for the difficulties in school-to work transitions, the individuals are held microscopically responsible for their unemployment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the preference of academically high-performing students towards VET has increased remarkably, and students from the top percentiles (top %1) have started to prefer VET programs in the last three years. In order to alleviate the skill mismatches in the labor market, new regulations have been made in order to balance the supply and demand in VET on a rational basis, and to increase the matching of VET high schools and institutions with the sector needs Suna et al, 2020).…”
Section: Vocational Education and Training In Turkeymentioning
confidence: 99%
“…This finding is attributed to the tendency of foreign-partnered companies to focus more on on-the-job training of employees. Suna et al (2020) investigated the reasons for horizontal skill mismatch by through interviews and questionnaire with VET graduates and found that the main reasons are graduates' inability to find sufficient open positions in their field, lack of difference in wages, employers' preference for experienced employees and working conditions. These findings indicated that the horizontal skill mismatch in VET in Turkey is largely due to labor market dynamics.…”
Section: Studies On Skill Mismatch In Turkeymentioning
confidence: 99%